“More Than Fruits and Vegetables”. Community garden experiences from the Global North to foster green development of informal areas in Sao Paulo, Brazil. - Aguiar Pedro, Alexandra; Görner, Anna; Lindner, André; Wende, Wolfgang (My University, 2020)
Urban gardening contributes to society in various ways such as by enhancingcommunities, ensuring food security, improving health, providing places forrecreation as well as by raising environmental awareness. Although urbangardening initiatives have been spreading, the challenge remains to includevulnerable communities, especially in developing countries, which facemanifold infrastructural, environmental and social pressures, thereby helpingachieve the United Nations Sustainable Development Goal (SDG) 11 (Makecities and human settlements inclusive, safe, resilient and sustainable) andfoster urban inclusiveness. The study evaluated the performance of urban community gardens in order to verify their potential for implementation in the slums of Sao Paulo, Brazil. Significant assets and drawbacks were analyzed from existing studies and categorized into social, spatial, economic and environmental factors. Additionally, qualitative interviews on societal and motivational issues were conducted with contributors to a community garden in Dresden, Germany.
Keywords: Großstadt; Urban Gardening; Urban Farming; Gemeinschaftsprojekt; Benachteiligter Stadtteil; Stadtentwicklung; Inklusion